Opposition to vaccination: a transatlantic discussion - Temte, Jonathan (Henry Stewart Talks, 2018)
Anti-vaccination movements in the US and the EU, The impact of vaccine opposition on the numbers of measles and influenza cases, The influence of public and social media on pro/anti-vaccines debate, Lack of public’s trust in the pharmaceutical industry and regulatory agencies in the US and the EU, The demographics of anti-vaccinators in the US and the UK, Challenges in communicating the safety and importance of vaccine to the public